COVID-19 and the role of estrogen in the immune response - Inna V. Dovzhikova; Irina A. Andrievskaya (Russian Open Medical Journal)
We conducted a study using the keyword search (estrogens and COVID-19) in various databases through June 2022. All articles were published in English. In the context of the COVID-19 pandemic, gender differences were found in the course and outcomes of the disease. The goal of this review was to summarize the knowledge of the mechanisms underlying gender-based differences in COVID-19, with a focus on the role of estrogens. The article discusses the involvement of estrogen in the implementation of the immune response to viral infection. Separate sections of the review are dedicated to the effect of estrogens on innate and adaptive varieties of immunity. We concluded that there is great potential for future research on deciphering the effect of hormones on human physiology and immune responses to explain the heterogeneity of human pathogenic responses.